2018
DOI: 10.5744/rhm.2018.1006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Perspectivalism in Patient Participation: An Evaluation of FDA Patient and Consumer Representative Programs

Abstract: Recent research in rhetoric of health and medicine (RHM) has worked to evaluate the effectiveness of patient inclusion initiatives in health policy decision-making. Extending this line of research, this article evaluates the extent to which the U.S. Food and Drug Administration's (FDA) patient and consumer representative programs meaningfully engage patient experiences. In so doing, this study provides directed and summative content analyses of pharmaceuticals policy deliberation at 163 FDA drug advisory commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Measures such as shared decision-making, use of decision aids, consumer representatives, and application of electronic and Internet-based facilities have been proposed. [21][22][23][24] Successful PE, however, will depend on the approach taken and contextual factors, including barriers such as cost, organizational culture, and population-specific restrictions, as well as structural facilitators such as government support. 25 There is a need to help patients make the best choice of hospital beyond the geographical limits.…”
Section: Discussionmentioning
confidence: 99%
“…Measures such as shared decision-making, use of decision aids, consumer representatives, and application of electronic and Internet-based facilities have been proposed. [21][22][23][24] Successful PE, however, will depend on the approach taken and contextual factors, including barriers such as cost, organizational culture, and population-specific restrictions, as well as structural facilitators such as government support. 25 There is a need to help patients make the best choice of hospital beyond the geographical limits.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore foreseeable that if sponsors avail of an advisory committee under this new framework that the agency would, consistent with its current practices, use that as a public forum for hearing and trying to attend to patient interests. The new law's allowance for an advisory committee to be convened may, in other words, amount to a public hearing wherein the agency is likely to struggle to balance meaningful and inclusive participation from those impacted by its decision 91 with its core function of ensuring the safety and efficacy of drugs. 92 A more optimal way to proceed given the vexed nature of withdrawals would be to take the decision out of FDA's hands altogether.…”
Section: Withdrawal Challenges In the Face Of Sponsor And Patient Opp...mentioning
confidence: 99%
“…Their entry draws on their critiques of the writing and argument quality in these reports and suggestions for better documentation processes. In a related setting, Graham, Kessler, Kim, Ahn, and Card (2018) observed that efforts to expand patient participation in FDA expert advisory boards ironically often “further marginalize” their opinions (p. 59). These observations highlight the essential function of expert discourses.…”
Section: Connecting To Technical Communicationmentioning
confidence: 99%